Some clay lamps from Central District of Nora (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
In this paper a small selection of clay lamps – able to highlight some of the problems still persisting in this pottery class’s study – will be analysed. The choice fell on some of the most peculiar ones for their decoration, typological classification and context of finding among the artifacts discovered during the latest researches carried out in the Central District of Nora: a punic type from “case a mare”, two rounded-nozzle lamp from Central Baths and “Casa del Direttore Tronchetti” and, from this latter domus, also one of the late Warzenlampen type.
Keywords: clay lamps; problems; Central District; Nora; punic; case a mare; rounded-nozzle lamp; Central Baths; Casa del Direttore Tronchetti; domus; late Warzenlampen type